2021
DOI: 10.1021/acscatal.1c01761
|View full text |Cite
|
Sign up to set email alerts
|

Size and Composition Dependence of Oxygen Reduction Reaction Catalytic Activities of Mo-Doped PtNi/C Octahedral Nanocrystals

Abstract: A variety of synthesis protocols for octahedral PtNi nanocatalysts have led to remarkable improvements in platinum mass and specific activities for the oxygen reduction reaction. Nevertheless, the values achieved are still only one tenth of the activity measured from Pt 3 Ni single-crystal (111) surfaces. These particles lose activity during potential cycling, primarily because of Ni leaching and subsequent loss of shape. Here, we present the syntheses and high catalytic oxygen reduction reaction activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 52 publications
1
44
1
Order By: Relevance
“…PtNi-6 had an ECSA of 33.5 m 2 g Pt −1 , a specific activity of 0.5 mA cm −2 and a mass activity of 0.32 A mg Pt −1 , whereas PtNi(Mo)-14 had an ECSA of 56.6 m 2 g PT −1 , a specific activity of 5.84 mA cm −2 , and a mass activity of 1.95 A mg Pt −1 . After accelerated stress testing the undoped PtNi-6 specific and mass activities improved but still did not reach the values of PtNi(Mo)-14 (Figure 2B) (Polani et al, 2021) Zhu et al found that alloying Pt with Ir to produce Pd@Pt-Ir core-shell nanocrystals resulted in better performance and stability compared to Pd@Pt/C materials. Pt and Ir were simultaneously deposited in thin layers over cubic, octahedral, and icosahedral Pd seeds with {100} and {111} facets.…”
Section: Seed-mediated Synthesis For Improved Stabilitymentioning
confidence: 99%
“…PtNi-6 had an ECSA of 33.5 m 2 g Pt −1 , a specific activity of 0.5 mA cm −2 and a mass activity of 0.32 A mg Pt −1 , whereas PtNi(Mo)-14 had an ECSA of 56.6 m 2 g PT −1 , a specific activity of 5.84 mA cm −2 , and a mass activity of 1.95 A mg Pt −1 . After accelerated stress testing the undoped PtNi-6 specific and mass activities improved but still did not reach the values of PtNi(Mo)-14 (Figure 2B) (Polani et al, 2021) Zhu et al found that alloying Pt with Ir to produce Pd@Pt-Ir core-shell nanocrystals resulted in better performance and stability compared to Pd@Pt/C materials. Pt and Ir were simultaneously deposited in thin layers over cubic, octahedral, and icosahedral Pd seeds with {100} and {111} facets.…”
Section: Seed-mediated Synthesis For Improved Stabilitymentioning
confidence: 99%
“…Second, alloying Pt with a less expensive 3d transition metal (Ni, Co, Cu, etc.) is a feasible method to improve the ORR intrinsic activity [16][17][18][19][20]. For example, Tian et al reported that 1D bunched PtNi alloy nanocages with a Pt-skin structure displayed a high activity and durability for ORR [21].…”
Section: Introductionmentioning
confidence: 99%
“…measured by cyclic voltammetry. [25][26][27] Yet, the discussion of stability requires additional measurements to determine dissolved cations, [28,29] as well as changes in the catalyst composition, [20,30] morphology [31][32][33] and structure. [34,35] Co-based ATMO have attracted particular attention due to their high catalytic activity.…”
Section: Introductionmentioning
confidence: 99%